OPTIMALISASI USAHA PENYEDIAAN LAHAN PEMAKAMAN DALAM KAWASAN PERUMAHAN DI KABUPATEN BOYOLALI - Yusuf Nunung Arifin (Jurnal Geografi : Media Informasi Pengembangan dan Profesi Kegeografian, 2016)
The the residential building, the existence of cemetery land is a requirement that must be met, but the existence ofcemetery land often not available to occupants of the residential. The existence of cemetery land should be optimal soas to boost the usefulness of cemetery land. To determine the level of optimization of the existing cemetery land in aresidential area in Boyolali Regency then conducted research with the aim to determine whether the residential sidewas optimal in supplying cemetery land and to know the work done of occupants of the residential related to the limitedof cemetery land and the way to determine the location of the cemetery. Technical analysis used in this research usingdescriptive quantitative methods with score techniques and supported by strengthening of qualitative data from theresults of key figures interviews. Results of the research showed 76.4% of the residential supply the cemetery land thatis not optimal and 23.4% supply the cemetery land facilities that are not optimal. The selection of the cemetery landwas likely to choose the village cemetery land and obstacles often encountered were the refusal of the villagers to usethe village graveyard. The conclusion in the form of 26 residential use of land owned by the village cemetery and 8 areabsolutely no cemetery land that can be used for residential residents. While the majority of the residential occupantschoose to use land owned by the village cemetery for their funeral procession.